Research on multiculturalism in nursing practice. A review of Polish nursing literature - Chałdaś-Majdańska, Justyna; Bieniak, Monika; Machul, Michał; Bąk, Jadwiga; Chrzan-Rodak, Agnieszka; Dobrowolska, Beata (Journal of Education, Health and Sport, 2017)
Introduction. The phenomenon of multiculturalism confronts nurses with new challenges. Therefore, scientific research on multicultural issues in nursing practice is of great importance. Their results can improve both education and clinical practice. Aim. The aim of this paper was to analyse the results of empirical studies available in the Polish academic nursing literature on multiculturalism in nursing practice Material and methods. The research involved a systematic review of the academic nursing literature from 2011-2016. The databases of ranked nursing journals and the Google Scholar database were searched by combination of the following keywords: multiculturalism; culturally different patient; nursing care; multicultural nursing; patient from another culture; cultural sensitivity in nursing care. Results. Searching process resulted with 14 papers that met the inclusion criteria. The dominant research method used was the survey method with the utilisation of authors’ questionnaire and standardized research tools. The study was conducted in different groups, e.g. foreign students, nursing students, health workers, representatives of local communities, followers of some religions and patients. Among the main issues in analyzed research were: the cultural competences of nursing staff, the impact of religious creed on the selected aspects of medical care, the standards of nursing education with regard to patients coming from different cultural backgrounds, the attitudes of Polish society to people from different cultural backgrounds, and the health-related behaviour of people representing different cultural areas. Conclusions. Polish nurses undertake scientific research on various aspects of multiculturalism in medical care. However, there is a need to introduce multidisciplinary and multi-centre scientific research tackling multiculturalism issues in medical care in a broader way.